Cleft sidedness and congenitally missing teeth in patients with cleft lip and palate patients - Abdolreza Jamilian; Alessandra Lucchese; Alireza Darnahal; Zinat Kamali; Letizia Perillo (SpringerOpen, 2016)
Abstract Background The aim of this study was to investigate the prevalence of cleft sidedness, and the number of congenitally missing teeth in regard to cleft type and gender. Methods The charts, models, radiographs, and intraoral photographs of 201 cleft patients including 131 males with the mean age of 12.3 ± 4 years and 70 females with the mean age of 12.6 ± 3.9 years were used for the study. T test, Chi-square, and binomial tests were used for assessment of the data. Results and conclusions One hundred forty-eight of the subjects suffered from cleft lip and palate followed by 41 subjects who suffered from cleft lip and alveolus. Chi-square test did not show any significant difference between the genders. Binomial test showed that left-sided cleft was more predominant in unilateral cleft lip and palate patients (P < 0.001). This study also showed that the upper lateral incisors were the most commonly missing teeth in the cleft area.